1979
DOI: 10.1126/science.451567
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Perfusion Rate Determined from the Decay of Oxygen-15 Activity After Photon Activation in Situ

Abstract: Rates of cerebral perfusion were obtained from measurements of the disappearance (wash-out) of oxygen-15 after in situ tissue activation with 45-million-volt x-rays. In an anesthetized cat, typical values were 90 milliliters per minute per 100 grams of tissue, with 55 percent wash-out. In a specific radiotherapy patient, the value was 65 milliliters per minute per 100 grams of tissue, with 63 percent wash-out of oxygen-15 through incorporation into tissue water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…3-D imaging of activity is recon-structed from the detection data of the planar detector by using maximum likelihood algorithm, taking into consideration the attenuation coefficient of 511 keV gamma rays in the patient's body calculated by the patient's CT image data. In the experiment using a 22 Na point source, position resolution of measured activity with the distance between detector heads of 50 cm was about 2 mm of the full width at half maximum at isocenter in the FOV. The change of the position resolution depending on the increase of the distance between detector heads is about 1 mm.…”
Section: Iib Beam On-line Pet System Mounted On a Rotating Gantry Pmentioning
confidence: 99%
See 1 more Smart Citation
“…3-D imaging of activity is recon-structed from the detection data of the planar detector by using maximum likelihood algorithm, taking into consideration the attenuation coefficient of 511 keV gamma rays in the patient's body calculated by the patient's CT image data. In the experiment using a 22 Na point source, position resolution of measured activity with the distance between detector heads of 50 cm was about 2 mm of the full width at half maximum at isocenter in the FOV. The change of the position resolution depending on the increase of the distance between detector heads is about 1 mm.…”
Section: Iib Beam On-line Pet System Mounted On a Rotating Gantry Pmentioning
confidence: 99%
“…And there are some reports that research washout effect of 15 O activity generated by photonuclear reaction using high-energy x-ray irradiation. 22,23 Our previous study mentioned the washout effect of liver of patient in proton therapy. 15 One of the deterioration of images obtained from the measured activity using BOLPs-RGp will be for the washout effect.…”
Section: Iiia Measured Activity Distributionsmentioning
confidence: 99%
“…Tissue activation was first discussed in detail by Tobias in 1949 7 and was first reported in gamma-ray experiments by Mayneord et al later that year. 8 Since then the radioactivity induced in tissues by photon, [8][9][10] proton, 11,12 neutron, 13 pion, [14][15][16] and heavy-ion radiotherapy beams [17][18][19] has been investigated. This induced activity has been studied as a source of patient dose, 11,20,21 as a means of determining elemental tissue composition, 10,11,13 and for determining dose distributions.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the sensitivity of the camera was very low and the output only analogous, no further such attempts were made (L Johansson, personal communication). Other early studies have shown the potential use of tissue activation for the analysis of tumor blood flow in animal studies [14-16]. More recently, by the study of biological washout processes of ion-beam-induced positron emitters, half-lives of various washout components could be measured in animals [10,11] and in patients [12,17].…”
Section: Resultsmentioning
confidence: 99%